2009
DOI: 10.1523/jneurosci.5746-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low-Conductance HCN1 Ion Channels Augment the Frequency Response of Rod and Cone Photoreceptors

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) ion channels are expressed in several tissues throughout the body, including the heart, the CNS, and the retina. HCN channels are found in many neurons in the retina, but their most established role is in generating the hyperpolarization-activated current, I h , in photoreceptors. This current makes the light response of rod and cone photoreceptors more transient, an effect similar to that of a high-pass filter. A unique property of HCN channels is thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 52 publications
8
96
1
Order By: Relevance
“…We found that deletion of HCN1 leads to prolonged rod responses in the ERG, together with a reduced flicker fusion frequency 13 . We concluded that this is due to the lack of HCN1 in rods, which is also supported by ex vivo tiger salamander data 26 and have developed a concept and a set of hypotheses to examine the nature of this phenomenon. We found that HCN1 channel feedback is of crucial importance under conditions when both rods and cones are active.…”
Section: Discussionsupporting
confidence: 61%
“…We found that deletion of HCN1 leads to prolonged rod responses in the ERG, together with a reduced flicker fusion frequency 13 . We concluded that this is due to the lack of HCN1 in rods, which is also supported by ex vivo tiger salamander data 26 and have developed a concept and a set of hypotheses to examine the nature of this phenomenon. We found that HCN1 channel feedback is of crucial importance under conditions when both rods and cones are active.…”
Section: Discussionsupporting
confidence: 61%
“…Further study can be performed to investigate the effect of overexpressing HCN channels in mESCs to elucidate the role of this I inst on the proliferation and cell cycle progression of mESCs. Nonetheless, hyperpolarization in the S phase is expected to result in one or both of the below scenarios: (1) activation of HCN channels and increase in I h which would in turn lead to depolarization and deactivation of the HCN channels, resulting in a decrease in I h at the end of S phase; (2) increase in the driving force for I inst which would in turn lead to depolarization, resulting in a decrease in driving force for I inst at the end of S phase. [4,6,26].…”
Section: Discussionmentioning
confidence: 99%
“…Rod and cone synapses function as band-pass filters (Armstrong-Gold and Rieke, 2003;Burkhardt et al, 2007). Although several presynaptic factors, including gap-junctional coupling, voltage-gated conductances, and synaptic release kinetics, likely contribute to this (ArmstrongGold and Rieke, 2003;Zhang and Wu, 2005;Burkhardt et al, 2007;Barrow and Wu, 2009), the role of synaptic vesicle replenishment has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%